2015
DOI: 10.5152/eurjrheum.2015.0012
|View full text |Cite
|
Sign up to set email alerts
|

Differential assay reactivity of immunglobulin A anti-ß2 glycoprotein I antibodies: implications for the clinical interpretation of antiphospholipid antibody testing

Abstract: Objective: The routine measurement of IgA anticardiolipin (aCL) and IgA anti-β 2 glycoprotein I (anti-β 2 GPI) antibodies remain controversial despite several studies demonstrating an association with thromboembolic disease in patients with systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS). This controversy may be a contributing factor for the current under use of IgA antiphospholipid antibodies. We aimed to investigate the nature of discrepant IgA anti-β 2 GPI reactivity to help define th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…IgA aPS/PT are statistically significantly associated to both arterial and venous thrombosis. No studies to date have investigated the prevalence and clinical significance of IgA antiprothrombin antibodies, but several studies have confirmed an association between IgA anti-β2GPI and an increased risk of thromboembolic vascular disease [2][3][4][5]27]. In agreement with the last international consensus [1] we also demonstrated association of IgA anti-β2GPI with thrombotic manifestations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…IgA aPS/PT are statistically significantly associated to both arterial and venous thrombosis. No studies to date have investigated the prevalence and clinical significance of IgA antiprothrombin antibodies, but several studies have confirmed an association between IgA anti-β2GPI and an increased risk of thromboembolic vascular disease [2][3][4][5]27]. In agreement with the last international consensus [1] we also demonstrated association of IgA anti-β2GPI with thrombotic manifestations.…”
Section: Discussionsupporting
confidence: 85%
“…The following literature on IgA antiphospholipid antibodies is quite diverse, reporting a high variability in its prevalence, as well as clinical significance. However, several experimental data published recently showed possible pathogenic roles of both IgA aCL and IgA anti-β2GPI [2][3][4][5][6][7]. These antibodies have been reported in up to 70% of patients with systemic lupus erythematosus (SLE) and in those with primary APS [8].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to standardize IgA-aB2GPI assays are definitely needed. [ 34 , 48 50 ] Further multicenter cohort study studies with patients of various ethnicities are required, to definitively determine the association between the IgA-aB2GP1 and APS-events in asymptomatic population before recommending preventive treatment with anticoagulants or platelet antiagregants drugs. The proposed formula to calculate patient-risk could be a helpful tool to make clinical decisions, however, before generalizing its use, these rules should be confirmed with multicenter studies and improved with the incorporation of additional markers such as the presence of circulating B2GP1 immune complexes.…”
Section: Discussionmentioning
confidence: 99%
“…A growing interest in aβ2-GPI IgA was observed over the last decade supporting: (i) that aβ2-GPI IgA are associated with APS and with a likelihood ratio that falls between IgM and IgG, indicating that aβ2-GPI IgG remains, without any doubt, the best isotype for the diagnosis of APS [123] [137] [144] [145] ; (ii) that a unique positivity of IgA represents the main independent predictive marker for thrombosis in patients who never had a history of APS (OR = 5,64 [2,46 -12,91]), before age, sex, diabetes and arterial hypertension in APS [146]; and (iii) that aβ2-GPI IgA determination already represents a validated immunological marker useful for the diagnosis of SLE regardless of the titers [147].…”
Section: Regarding the Aβ2-gpi Iga Isotypementioning
confidence: 99%